PENGARUH JENIS MEDIA SERBUK KAYU DAN DOSIS DOLOMIT TERHADAP PERTUMBUHAN DAN HASIL JAMUR TIRAM PUTIH (PLEURETUS OSTREATUS) - PUTRA, ANAK AGUNG GEDE; LANA, WAYAN; SUKASANA, I WAYAN; KARNATA, I NENGAH (GANEC SWARA, 2024)
This study aims to determine the effect and interaction of types of sawdust and mixed doses of dolomite on the growth and yield of white oyster mushroom (pleurotus osteatus). This study used a Randomized Block Design (RAK) with 2 factors, namely the composition of the planting medium of sawdust (albezia sawdust, cempaka sawdust, mahogany sawdust) and a mixture of dolomite doses. This research was conducted at the Parent Seed Center for Horticultural Food Crops (UPTD BBITPH) Luwus Village, Baturiti District, Bali Province. This research was conducted from May 2022 to July 2022. The results of statistical analysis showed that the interaction between the composition of the growing media and dolomite (S x C) had a very significant effect (P 0.01) on the parameters of the number of fruiting bodies per clump (hood), size stem diameter (mm) and oven-dry weight of mushroom fruit (g). There was no significant effect (P 0.05) on pinhead growth, fruit body stalk length (mm), mushroom fruit cap diameter thickness (mm) and mushroom wet weight (g). The highest mushroom oven dry weight was obtained from the media composition of Sc (chrysolite wood powder) Dolomite C4 which was 11.85 g and the lowest was obtained in the treatment of the media composition Sa (Albezia wood powder) dolomite C2 of 5.38 g